377 The prescription drug epidemic in the United States – efforts to improve prescribing. (1st September 2016) - Baldwin, Grant; Houry, Debra; Noonan, Rita
Abstract : Background: More than 145, 000 people have died from overdoses involving prescription opioid pain relievers in the United States in the last decade and deaths have quadrupled since 1999. The quantity of opioids sold in the United States in 2011 was four times that sold in 1999. Providers wrote more than a quarter of a billion opioid prescriptions for Americans in 2012. Description of the Problem: While opioid pain relievers can and do play an important role in the management of some types of pain, the overprescribing of these powerful drugs for chronic, non-cancer pain outside of end-of- life care created and continues to fuel the epidemic. The U.S. Centres for Disease Control and Prevention (CDC) implemented a comprehensive suite of interventions to: (1) strengthen state efforts by scaling up effective, data-driven public health interventions; and (2) enhance patient safety by supplying health care providers with information, tools, and guidance for evidence-based decision making. Results: Beginning in September 2015, the CDC launched the Prevention for States program. A total of 16 states were funded to enhance and maximise state-based prescription drug monitoring programs, advance effective prevention efforts in hard hit communities, and improve health system and insurer practices to improve opioid prescribing. Early progress highlights the necessity of collaboration and that significant strides can be made when the barriers and silos within a state are eliminated. CDC also released guidelines to primary care providers for opioid prescribing for chronic pain outside of end-of-life care in January 2016. Broad dissemination is underway. Conclusion: With opioids among the most prescribed drugs in the United States, a substantial investment is needed to shift opioid prescribing to make it safer and to improve patient care. CDC's multifaceted and evidence-based interventions are making a difference. Highlights and lessons learned from CDC activities will be shared.